Den mediala barnkammaren: Hur barn använder och förhåller sig till medier - Hyltén-Cavallius, Charlotte (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
How do children aged eight to eleven relate to and handle media today? And how do their parents and other grownups relate to the children’s use of media? Are there any differences in use and relationship to media between children growing up in different places in the greater Stockholm? This article is based on interviews with over a hundred children in five different places, drawings and toys. The study was a follow up by a media critical study carried out by Eva Lis Bjurman in the 1970´s that studied the effects of segregation on children’s leisure activities in different parts of Stockholm. The 1970’s perspective viewed the children as passive receivers of messages and interpreted the working class children as victims of mass culture. In this study class, or more specifically how class is performed in terms of choices concerning media, clothes and activities, has guided the analysis. It is rooted in a tradition within childhood research that sees the child as being in the world and not as becoming something. But viewing children as capable of interpreting culture isn’t enough. The children’s narratives have to be interpreted in a societal and historical context. By doing that the study shows that the same structural class related patterns showed by Bjurman still is very vivid and related to certain places – e.g. that the middle class children at every instance receive a much wider range of cultural products and experiences than other children and are taught to make social and cultural distinctions by their parents.